Never seduce a duke - Lorret, Vivienne (Lorret, Vivienne. Mating habits of scoundrels, 2023)
Mistaken for a notorious thief known for seducing men to distraction while on holiday, Margaret Stredwick, longing for adventure, eagerly plays along until she returns to her ordinary life, soon discovering that her grand flirtation with the Duke of Merleton won't be secret for long.